PENGARUH KETERAMPILAN DAN ETOS KERJA TERHADAP PRODUKTIVITAS KERJA PADA CV MANDIRI TRANS DI SURABAYA - Yunni Rusmawati DJ (Media Mahardhika, 2020)
Employees are the main asset of the company who become planners and active actors of every organizational activity. They have the thoughts, feelings, desires of status, and educational background, age, and gender that are heterogeneous which are brought to the company organization. Employees are not machines, money, and materials that are passive in nature and can be fully controlled and regulated in order to support the achievement of company goals. The purpose of this study was to partially determine the variables of skills and work ethic factors on productivity at CV Mandiri Trans in Surabaya, to determine the simultaneous influence of the variables of skills and work ethic factors on productivity and to determine the variables of skills and factors. Work ethic that has the most dominant influence on productivity at CV Mandiri Trans in Surabaya. The population in this study amounted to 30 so that the samples taken were all the numbers of the population using saturated sampling techniques. The data analysis method used was the validity test, reliability test, multiple linear regression analysis, t test and F test. The results obtained in this study were Y = 4.851 + 0.355 X1 + 0.515X2 so that it states that the most dominant variable affects Work productivity is a work ethic variable with a regression coefficient of 0.515.